2012
DOI: 10.4103/0970-9185.92451
|View full text |Cite
|
Sign up to set email alerts
|

Effect of magnesium sulfate with propofol induction of anesthesia on succinylcholine-induced fasciculations and myalgia

Abstract: Background:Magnesium sulfate and propofol have been found to be effective against succinylcholine-induced fasciculations and myalgia, respectively, in separate studies. A prospective randomized double blind controlled study was designed to assess the effect of a combination of magnesium sulfate with propofol for induction of anesthesia on succinylcholine-induced fasciculations and myalgia.Materials and Methods:Randomly selected 60 adult patients scheduled for elective surgery under general anesthesia were allo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 31 publications
2
19
2
Order By: Relevance
“…Our findings are supported by findings of Mahendra Kumar et al (2012) who reported 30% postoperative myalgia in control group compared to none in magnesium sulphate group. 16 Our study is in contrast to the findings of R Ursekar et al (2016) who reported no significant difference in postoperative myalgia between control group and the group receiving magnesium sulphate. 20 Our study is also supported by the study of McClymont C (1994) who found significantly lower incidence of suxamethonium myalgia (19%) compared with thiopentone group (63%) (P<0.05).…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…Our findings are supported by findings of Mahendra Kumar et al (2012) who reported 30% postoperative myalgia in control group compared to none in magnesium sulphate group. 16 Our study is in contrast to the findings of R Ursekar et al (2016) who reported no significant difference in postoperative myalgia between control group and the group receiving magnesium sulphate. 20 Our study is also supported by the study of McClymont C (1994) who found significantly lower incidence of suxamethonium myalgia (19%) compared with thiopentone group (63%) (P<0.05).…”
Section: Resultscontrasting
confidence: 99%
“…with statistically significant difference between two groups (P<0.001) ( reported fasciculations in 100% of placebo group and 50% in magnesium sulphate group. 16 We observed fasciculations in 66.7% cases in magnesium sulphate group and 100% cases in control group. Our findings are supported by the findings of Sakuraba S et al (2007) who also reported no fasciculations in 33% of magnesium sulphate group.…”
Section: Resultsmentioning
confidence: 56%
See 1 more Smart Citation
“…[9] Despite its limitations and side effects, succinylcholine is still a drug of choice for endotracheal intubation in operating rooms. [23] Fasciculation is an adverse effect of succinylcholine that may be a very unpleasant experience for patients.…”
Section: Discussionmentioning
confidence: 99%
“…Though postoperative myalgia was described at the beginning of the 1950s the pathogenesis is still unclear (37). For prevention a variety of methods, such as low dose of ND-NMBA (37,38), lidocaine (39), magnesium (40), dexmedetomidine (41) and gabapentin (42), have been suggested before administration of SCh. However, postoperative myalgia has still not been completely prevented.…”
Section: Thoughts Of Anaesthesiologists On the Use Of Schmentioning
confidence: 99%